Relação entre a reatividade de pontos de acupuntura e atividade física com afecções ortopédicas determinadas por exames de imagens em equinos - Sousa, Nicole Ruas de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to evaluate the reactivity of acupuncture points by pressure algometer and the relation between physical activity and orthopedic lesions in horses. It was analyzed 116 horses of dressage, racing, polo pony, reproduction/at rest, jumping, work and western performance with lameness confirmed by image diagnosis for reactivity of acupoints with grade 0 when the answer was normal, I, small, II moderate and III, intense, with evasive response, bite or kick, which only II and III were correlated to site of injury by chi square test, and physical activity with type and site of injury by Fisher test. Kruskall-Wallis test was performed, followed by Dunn's test to evaluate the relation between reactivity I, II and III with the pressure algometer. Desmitis were more prevalent in racehorses, western and work, and fractures in racehorses and polo pony. Stifle injuries were more prevalent in dressage than work, shoulder injuries were more prevalente in jumping than work. Hind tendon injuries were less prevalente in jumping than dressage, western and reproduction/at rest. 5336 measurements were performed in 23 bilateral acupoints. The overall mean values pressure algometer was 26 ± 6.43 N and the median corresponding to fingerprints of grades I, II and III were 24, 22 and 20 N, respectively, with significant difference between them, suggesting that palpation has a good correspondence with the pressure algometer to assess the reactivity of acupuncture points. We conclude that there is a relationship between location and type of injury with physical activity and palpation assessment of acupuncture points is helpful in identifying some structures injuries

Objetivou-se avaliar a reatividade de pontos de acupuntura por pressoalgímetro e a relação da atividade física com lesões ortopédicas em cavalos. Avaliaram-se 116 cavalos de adestramento, corrida, polo, reprodução-repouso, salto, trabalho e western com claudicação e confirmação do diagnóstico por imagem quanto à reatividade dos pontos de acupuntura, atribuindo graus de 0 quando a resposta era normal ou ausente, I, pequena, II, moderada e III, intensa, com resposta evasiva, mordedura ou coice, no qual apenas II e III foram correlacionados com o local da lesão pelo teste de qui quadrado, e a atividade física com o tipo e local de lesão pelo teste de Fisher. Foi realizado teste de Kruskall-Wallis seguido pelo teste de Dunn para avaliar a relação das reatividades I, II e III com o pressolagímetro. Desmites foram maiores em animais de corrida, western, e trabalho, e fraturas em animais de corrida e polo. Lesões de joelho foram maiores em adestramento que trabalho e de ombros maiores em salto que trabalho. Lesões tendíneas pélvicas foram menores em salto que adestramento, western e reprodução/repouso. Foram realizadas 5.336 mensurações em 23 acupontos bilaterais. A média geral dos valores do pressoalgímetro foi de 26 ± 6,43 N e as medianas correspondentes às pressões digitais de graus I, II e III foram de 24, 22 e 20 N respectivamente, com diferença significativa entre as mesmas, o que indica que a palpação apresenta uma boa correspondência com o pressoalgímetro para avaliar a reatividade dos pontos de acupuntura. Conclui-se que há relação entre local e tipo de lesão com atividade física e a avaliação palpatória dos pontos de acupuntura é útil na identificação de lesões de algumas estruturas
Relation between age, breed, type and local of orthopedic injuries with sport modalities and evaluation of reativity of acupunture points in horses
Keywords: Ortopedia veterinaria; Acupuntura veterinaria; Claudicação em eqüinos; Articulações - Ferimentos e Lesões; Medicina oriental; Cavalo; Lameness in horses; Veterinary acupuncture